Impact of Intraoperative Acetaminophen Administration on Postoperative Opioid Consumption in Patients Undergoing Hip or Knee Replacement - Raiff, Doug (Hosp Pharm, 2014)
Background: Opioid utilization for acute pain has been associated with numerous adverse events, potentially resulting in longer inpatient stays and increased costs. Objective: To examine the effect of intravenous (IV) acetaminophen administered intraoperatively on postoperative opioid consumption in adult subjects who underwent hip or knee replacement. Methods: This retrospective cohort study evaluated postoperative opioid consumption in 176 randomly selected adult subjects who underwent hip or knee replacement at Duke University Hospital (DUH). Eighty-eight subjects received a single, intraoperative, 1 g dose of IV acetaminophen. The other subjects did not receive any IV acetaminophen. This study evaluated mean opioid consumption (in oral morphine equivalents) during the 24-hour postoperative period in the 2 groups. Other endpoints included length of stay in the postanesthesia care unit (PACU), incidence of oversedation, need for acute opioid reversal, and adjunctive analgesic utilization. Results: Subjects who were given a single dose of intraoperative acetaminophen received an average of 149.3 mg of oral morphine equivalents during the 24 hours following surgery compared to 147.2 mg in participants who were not exposed to IV acetaminophen (P = .904). The difference in average length of PACU stay between the IV acetaminophen group (163 minutes) and those subjects not exposed to IV acetaminophen (169 minutes) was not statistically significant (P = .588). No subjects in the study experienced oversedation or required acute opioid reversal. Conclusion: There was not a statistically significant difference in postoperative opioid consumption between patients receiving and not receiving IV acetaminophen intraoperatively.